Differences in Motivation to Engage in Sexual Activity Between People in Monogamous and Non-monogamous Committed Relationships - Kelberga, Anna (Kelberg); Martinsone, Baiba (Frontiers in Psychology, 2021)
This study compared motivations to engage in sex between monogamous and non-monogamous respondents (n = 1,238, out of which 641 monogamous and 596 non-monogamous respondents; women—47.4%, men—50.9%, other gender—1.7%; age: M = 27.78 years, SD = 7.53, range = 18–62). The research aim was to identify whether there are differences in self-reported reasons to engage in sexual activity between these two groups. Presented with 17 reasons to engage in sexual activity, the respondents rated the frequency with which they engage in sex for each reason. While both monogamous and non-monogamous respondents reported to engage in sex with the same frequency for the reasons of sexual release and physical desirability of a partner, the research uncovered that non-monogamous respondents engage in sex significantly more often to seek new experiences, to boost self-esteem, to guard their mate, to have a specific kind of sex (such as anal, kink, or fetish) or to experience the thrill of the forbidden. Non-monogamous respondents reported higher frequency to engage in sex for most reasons overall. The study also revealed that there are differences in reasons to engage in sex among men and women, some of the differences are related to the relationship status (monogamous or non-monogamous), while others are universal for men or women irrespective of their monogamy status.